The Effect of Financial Knowledge, Financial Self-Efficacy, and Financial Attitude on MSMEs’ Capital Budgeting Decisions (E-Jurnal Akuntansi, 2025)
This study examines how financial knowledge, financial self-efficacy, and financial attitude affect capital budgeting decisions in micro, small, and medium enterprises (MSMEs) in Bandar Lampung. MSMEs play an important role in the Indonesian economy, but currently MSMEs still face challenges in financial management, especially in terms of capital budgeting. A quantitative method was used in this study, and primary data was collected from 398 MSME respondents selected through purposive sampling. The data were tested for validity, reliability, and classical assumptions before being analyzed using multiple linear regression. The results show that all three variables, both partially and simultaneously, have a positive impact. These findings support the Theory of Planned Behavior and emphasize the importance of improving financial knowledge, financial self-efficacy, and financial attitude for MSMEs to make rational, strategic, and sustainable decisions.